Faktor Yang Mempengaruhi Transformasi Tenaga Kerja Pertanian dan Dampaknya Terhadap Pendapatan Rumah Tangga Petani di Kawasan Wisata Hutan Pantai Cemara - Ariandi, Gugum; Dasipah, Euis; Ramdan, Moch (Papanda Publisher, 2024)
The objective of this research is to examine the determinants that impact the decision-making process of farmers to shift from agricultural labor to non-agricultural labor and its consequences on the income of farmer households (FH). The sampling method employed was simple random sampling, based on Slovin's formula, resulting in a sample size of 65 individuals. The statistical techniques used for analysis were multiple logistic regression and unpaired t-test. The findings reveal that farmer households (RTP) residing in the vicinity of Cidaun Beach tourist area have witnessed a shift in their employment from agriculture to non-agriculture, while agriculture remains their primary business. The non-agricultural sector offers several business and job opportunities, including retail, small shops, lending services, and motorbike rental services. Agricultural income contributes to 46.26% of the total household income, while non-agricultural income contributes to 53.74%. The shift from agricultural to non-agricultural labor is influenced by various factors, such as age, land area, land productivity, farmer knowledge, farmer income, and family responsibilities. Land area, farmer income, and dependency ratio are the primary determinants of the workforce's transformation. The shift from agricultural to non-agricultural labor has a significant impact on the increase in FH income, with a rise of 51.90%, primarily due to higher income from non-agriculture than agriculture.